(untitled) (The Macau Ricci Institute Journal, 2020)
Until now, during his pontificate Pope Francis has written three encyclicals: Evangelii Gaudium (2013), Laudato Si’ (2015), and Fratelli Tutti (2020). The central themes of each are: “We are all missionaries” in Evangelii Gaudium ; “Man as a part of Natural Environment” in Laudato Si’ ; and “Fraternity and Solidarity” in Fratelli Tutti .Searching for the underlying message of these three encyclicals, we realize that they convey the "Way" (El Camino , in Spanish) Pope Francis has chosen to show us guiding our own mission in life: achieving happiness in the context of Catholic Church teachings, contributing to the society’s well-being. In what follows I will address three questions about the way the teachings of the three encyclicals are followed in Macau on a daily basis.